Chemical constituents of Prismatomeris malayana Ridley and quantitative structure activity relationship study on anti-inflammatory agents and their analogues / Nor Hayati Abdullah - Abdullah, Nor Hayati (2014)
Prismatomeris malayana Ridley of Rubiaceae was investigated for its anti-inflammatory properties by evaluating their inhibition of the hyaluronidase and lipoxygenase activity and of TPA-induced inflammation in mice. The leaf was found to be the most active in the three selected assays. From bioassay guided fractionation and isolation, ursolic acid 60 was isolated and found to be the compound responsible for the hyaluronidase inhibitory activity. The isolation work on the leaves yielded five pentacylic triterpenoids (PTC) (3β-hydroxyurs-12-en-28-oic acid 60 [ursolic acid], 3β, 19, 24-trihydroxyurs-12-en-28-oic acid 61 [barbinervic acid], 3β,23-dihydroxyurs-12-en-28-oic acid 62, 28-O-β-glucopyranosyl-3α,19α,23-trihydroxyurs-12-en-28-oic acid 63 and 3β-hydroxyurs-11-en-13,28-olide 65); three iridoids (asperulosidic acid 68, scandoside 70 and prismalayanoside 66). Compound 66 (prismalayanoside) is novel with an unprecedented spiro-octa-lactone ring. The ten compounds isolated from the roots are; one PTC (3β-hydroxyolean-12-en-28-O-acetoate 64); eight anthraquinones (lucidin-3-methyl ether 71, rubiadin-1-methyl ether 11, damnacanthol 72, rubiadin 10, 1-ethyl-3-hydroxymethyl-4-hydroxy-9,10-anthraquinone 73, 2-methoxy-3-oxyhydroxymethyl -9,10-anthraquinone 74, and lucidin-ω-methyl ether 21) and one iridoid (asperulosidic acid 68). Further investigation of the stems led to the isolation of lucidin-ω-methyl ether 21 (an anthraquinone) and asperuloside 69 (an iridoid). Seven analogues (75-81) were prepared by structural modification of ursolic acid 60. The quantitative structure activity relationship study (QSAR) was carried out to correlate the selected twenty two ursolic acid analogues with their hyaluronidase inhibitory activity. The statistical characteristic provided by the best multi linear model gave R2 value of more than 0.9 thus indicating good predictive ability.